2015
DOI: 10.1371/journal.pone.0145400
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 and Notch Pathways Interact and Control Biliary Morphogenesis

Abstract: BackgroundLKB1 is an evolutionary conserved kinase implicated in a wide range of cellular functions including inhibition of cell proliferation, regulation of cell polarity and metabolism. When Lkb1 is inactivated in the liver, glucose homeostasis is perturbed, cellular polarity is affected and cholestasis develops. Cholestasis occurs as a result from deficient bile duct development, yet how LKB1 impacts on biliary morphogenesis is unknown.Methodology/Principal FindingsWe characterized the phenotype of mice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
(50 reference statements)
2
25
0
Order By: Relevance
“…Here, we showed that LKB1 is overexpressed in CTNNB1 ‐mutated HCC relative to nonmutated HCC and that aberrant activation of β‐catenin signaling induces post‐transcriptional accumulation of LKB1. Using an Lkb1 transcriptomic signature that we recently established using a liver‐specific deletion of Lkb1 in embryonic liver , we confirmed that CTNNB1 ‐mutated HCC express an LKB1 program. In addition, we found that LKB1 is required for specific physiological functions of β‐catenin in the liver and exerts a physiological role as a positive modulator of β‐catenin‐dependent metabolic zonation.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Here, we showed that LKB1 is overexpressed in CTNNB1 ‐mutated HCC relative to nonmutated HCC and that aberrant activation of β‐catenin signaling induces post‐transcriptional accumulation of LKB1. Using an Lkb1 transcriptomic signature that we recently established using a liver‐specific deletion of Lkb1 in embryonic liver , we confirmed that CTNNB1 ‐mutated HCC express an LKB1 program. In addition, we found that LKB1 is required for specific physiological functions of β‐catenin in the liver and exerts a physiological role as a positive modulator of β‐catenin‐dependent metabolic zonation.…”
Section: Introductionsupporting
confidence: 59%
“…LKB1KO livemb mutant and control and mice were 3 weeks old. (B) Heat map of the liver β‐catenin target gene signature from the gene expression profile of LKBKO Livemb mice . (C) RT‐qPCR analysis of various positively ( Axin2 , Sp5 , Glul , Lect2 , Cyp2e1 , Nkd1 ) regulated β‐catenin target genes in 14‐day‐old control and LKBKO livemb mutant mice.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that LKB1 loss leads to dysregulation of Notch and results in disorganized ductal structures (33). Ducts in the LKO mice were reported to be primitive ducts that lack symmetry with no frank disruption of parenchymal hepatocyte organization (17, 33).…”
Section: Resultsmentioning
confidence: 99%
“…Ducts in the LKO mice were reported to be primitive ducts that lack symmetry with no frank disruption of parenchymal hepatocyte organization (17, 33). We analyzed the Notch signaling profiles in the Pten null livers (GSE70501) using gene set enrichment analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation